The Identification of Relevant Factors for Breastfeeding Techniques in Postpartum Women Before Discharge in China: A Cross-Sectional Study - Sen Li; Dan Zhu; Guoli Liu (IMR Press, 2023)
Background: To assess breastfeeding techniques and identify the relevant factors among postpartum women in hospital. Methods: A cross-sectional study was conducted from March, 2022 to April, 2022 at a general hospital in China. A total of 331 postpartum women were investigated using a questionnaire survey that included the LATCH (latch, audible swallowing, type of nipple, comfort, and hold) scoring system, a general information and behavior questionnaire, a breastfeeding knowledge questionnaire, and the Chinese version of the maternal breastfeeding evaluation scale. Multiple regression analysis was used to identify independent factors for in-hospital breastfeeding techniques. Results: The average score for breastfeeding techniques before discharge was 7.88. In the bivariate analysis, the factors found to be significantly associated with scores for breastfeeding technique were parity, number of births, participation in online antenatal classes during pregnancy, mastery of the hand expression technique, nipple cracking and satisfaction with breastfeeding (each p < 0.05). The result displayed parity, participation in online antenatal classes, and satisfaction with breastfeeding were included in a multiple linear regression model (p < 0.05). Conclusions: Although breastfeeding techniques prior to discharge are improving, more improvements can be made. Clinical medical staff should therefore pay particular attention to primiparas, postpartum women who did not participate in online antenatal courses during pregnancy, and postpartum women with a low satisfaction for breastfeeding. Measures that promote breastfeeding techniques, publicize online antenatal training courses, provide breastfeeding guidance shortly after delivery, and provide timely evaluation and targeted guidance should help to improve breastfeeding techniques before discharge and increase the exclusive breastfeeding rate.